An evaluation of the accuracy of Root ZX according to the conditions of major apical foramen - Shin-Young Park; Dong-Kyun Lee; Ho-Keel Hwang (Restorative Dentistry & Endodontics, 2012)
Objectives The purpose of this study was to assess the accuracy of Root ZX (J. Morita Corp.) according to the location of major foramen and open apex.